A COMPARATIVE ANALYSIS OF THE INTERNATIONAL STANDARDS FOR THE PROFESSIONAL PRACTICE OF INTERNAL AUDITING AND THE GLOBAL INTERNAL AUDIT STANDARDS (GIAS) - Eyad Alhendi (PEOPLE: International Journal of Social Sciences, 2025)
In January 2024, the Institute of Internal Auditors (IIA) issued the Global Internal Audit Standards (the Standards) with implementation required by January 9, 2025. These standards represent a significant update from the 2017 version (the International Standards for the Professional Practice of Internal Auditing ), introducing several key changes to enhance the internal audit profession (IIA, 2025). This paper focuses on explaining the critical updates on the new global internal audit standards (GIAS).These standards are related to many areas such as, standards structure, internal audit functions, emerging risks, strategic objectives, artificial intelligence, and cybersecurity.